Elaboración y evaluación farmacognóstica , fitoquímica , farmacológica y toxicidad aguda oral preclínica de un té de moringa oleífera. - Placencio Franco, Ruddy Estefania (2015)
The present study aimed to develop and evaluate parameters farmacognostico, phytochemical, pharmacological and preclinical oral acute toxicity of tea of Moringa oleifera. It was leaves of Moringa oleifera as harvested active principle in the academic unit of agricultural sciences of the UTMACH, bark of pineapple, Orange, and dehydrated lemon flavoring and Stevia as a sweetener, acquired in the central market of Machala. Tests were performed to establish the optimum formulation of tea, pilots of formulations by varying the concentration of its components.